Theoretical, thermodynamic and electrochemical analysis of biotin drug as an impending corrosion inhibitor for mild steel in 15% hydrochloric acid - Xu, X.; Singh, A.; Sun, Z.; Ansari, K.R.; Lin, Y. (Royal Society Publishing, 2017)
The corrosion mitigation efficiency of biotin drug for mild steel in 15% hydrochloric acid was thoroughly investigated by weight loss and electrochemical methods. The surface morphology was studied by the contact angle, scanning electrochemical microscopy, atomic force microscopy and scanning electron microscopy methods. Quantum chemical calculation and Fukui analysis were done to correlate the experimental and theoretical data. The influence of the concentration of inhibitor, immersion time, temperature, activation energy, enthalpy and entropy has been reported. The mitigation efficiency of biotin obtained by all methods was in good correlation with each other. Polarization studies revealed that biotin acted as a mixed inhibitor. The adsorption of biotin was found to obey the Langmuir adsorption isotherm. Surface studies showed the hydrophobic nature of the steel with inhibitor and vindicated the formation of a film on the metal surface that reduced the corrosion rate. © 2017 The Authors.
Keywords: biotin; SECM; AFM; electrochemical; corrosion inhibitor; quantum calculations